Castaway from Rhodes - Cervon, Jacqueline; Niklaus, Thelma (New York : Franklin Watts, 1969)
Washed up on Turkish shores after a storm, a Greek boy becomes friends with a Turkish boy despite the hostilities between their two countries
Keywords: Prejudices; Friendship